Social Media, Opinion Polls, and the Use of Persuasive Messages During the 2016 US Election Primaries. (July 2018) - Rossini, Patrícia; Hemsley, Jeff; Tanupabrungsun, Sikana; Zhang, Feifei; Stromer-Galley, Jennifer
Political campaigns' use of digital technologies has been a topic of scholarly concern for over two decades, but most studies have been focused on analyzing the use of digital platforms without considering contextual factors of the race, like public opinion polls. Opinion polls are an important information source for citizens and candidates and provide the latter with information that might drive strategic communication. In this article, we explore the relationship between the use of social media in the 2016 US presidential elections and candidates' standing in public opinion polls, focusing on the surfacing and primary stages of the campaign. We use automated content analysis to categorize social media posts from all 21 Republican and Democratic candidates. Results indicate that a candidate's performance in the polls drives certain communicative strategies, such as the use of messages of attacks and advocacy, as well as the focus on personal image.